Model Pembelajaran Kooperatif Tipe GI ( Group Investigation) untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Hellen Candana Putri; Mery Cyntia; Novan Yakhin Gamaliel (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study was motivated by the need for modern education to develop students' creative thinking skills, which are still hampered by the dominance of conventional teacher-centred learning methods. The Group Investigation (GI) cooperative learning model is seen as a strategy that can encourage active participation, collaboration, and independent investigation among students. This study aims to describe the GI concept, its elements and principles, implementation steps, as well as its strengths and weaknesses in the context of learning. The research method used is a literature study through theoretical analysis and GI implementation experiences as described in the paper. The results of the study show that GI increases learning activities, critical and creative thinking skills, and students' social skills through heterogeneous group work and a structured investigation process. However, this model requires more time and teacher readiness in managing the class. The implications of this study confirm that GI is relevant to the Merdeka Curriculum and can be an effective alternative for collaboration- and project-based learning.